Application of cubic spline interpolation in communication engineering - ANGDaiji SUO (Dianxin kexue)
In the communication engineering practice,it often needs to estimate the unknown samples which are missing with the limited samples,then the interpolation operation is needed.Based on the research of cubic spline interpolation,the validity was given in communication engineering applications of the cubic spline interpolation by the experimental results on free space loss calculation,feeder insertion loss estimation,correlative interferometer.